Pulse jet engine / Denni Pusin - Pusin, Denni (2004)
As a final year project, the group decided to design, fabricate and test a pulse jet engine. The design was targeted to produce 1.5kg of static thrust. As there is no design guidelines or textbook material regarding pulse jet engine available for reference, it was decided that data of historically functional pulsejet engines was collected and empirically correlated. The data collected include produced thrust, dimensions of pulsejet engine components (viz. tail pipe length, diameter) and valve flow area. All components were designed and fabricated from sketch. The pulsejet engine was successfully assembled. Testing was carried out using different fuels. The pulsejet failed to ignite with kerosene and gasoline due to the difficulty in getting the correct proportion of air: fuel mixture. Subsequently, liquefied petroleum gas, LPG was selected based on its wider flammability limits. After repeated toiling with different design parameters such as reed valve design and valve retainer angle, the pulsejet engine finally successfully started. However, the engine can only run continuously under constant supply of air from a vacuum cleaner. This can be sustained for about 15 to 20 seconds before the front of the engine caught fire. This was due to leakage or wear from the reed valve to the mixing inlet cone of the engine.